2012
DOI: 10.1136/bcr.01.2012.5577
|View full text |Cite
|
Sign up to set email alerts
|

A pelvic mass on ultrasonography and high human chorionic gonadotropin level: not always an ectopic pregnancy

Abstract: A 24-year-old patient with 7-week amenorrhoea consulted for vaginal bleeding without abdominal pain. Ultrasonography revealed a 7 × 4 cm solid right pelvic mass. There was no visible intrauterine gestational sac. The serum β-human chorionic gonadotropin (β-hCG) level was 11 998 IU/l. Emergency laparoscopy was performed for a presumptive diagnosis of ectopic pregnancy. At laparoscopy, the right ovary was enlarged with a non-haemorrhagic 7 × 4 cm solid lesion, which was resected. The histological diagnosis was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…On literature review, we found 5 similar case reports of neoplasms mimicking ectopic pregnancy. Two mixed germ cell tumors ( Ozkaya et al, 2005 , Rozenholc et al, 2012 ), one mature teratoma ( Dawley et al, 2012 ), one ovarian choriocarcinoma ( Balat et al, 2004 ), and one mediastinal germ cell tumor that did not involve the adnexa ( Rivera et al, 2011 ). Malignant germ cell tumors make up less than 1% of ovarian cancers and rarely have an embryonal carcinoma component.…”
Section: Discussionmentioning
confidence: 99%
“…On literature review, we found 5 similar case reports of neoplasms mimicking ectopic pregnancy. Two mixed germ cell tumors ( Ozkaya et al, 2005 , Rozenholc et al, 2012 ), one mature teratoma ( Dawley et al, 2012 ), one ovarian choriocarcinoma ( Balat et al, 2004 ), and one mediastinal germ cell tumor that did not involve the adnexa ( Rivera et al, 2011 ). Malignant germ cell tumors make up less than 1% of ovarian cancers and rarely have an embryonal carcinoma component.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may overlook this fact and misinterpret tumor-producing factors as hormonal disturbances, as in a recently published case report of a woman of fertile age with a 7-week period of amenorrhea, who consulted for vaginal bleeding. A pelvic mass along with elevated βHCG was misinterpreted for an ectopic pregnancy but proved to be an ovarian DG with nests of syncytiotrophoblastic cells (28). Other atypical presentations of OGCT include cases mimicking pubertas tarda, where in 1 case a pubertal female with primary amenorrhea, short stature, and a vaginal septum proved to have 45,X/46,XY mixed gonadal dysgenesis with DG arising from gonadoblastoma (GB) (29).…”
Section: Introductionmentioning
confidence: 99%